USM ARCHITECTURE DEGREE RECOGNISED BY INTERNATIONAL PROFESSIONAL BODY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 22 January 2016 – Two Architectural degrees from Universiti Sains Malaysia (USM) have now been recognised and accredited by the worldrenowned professional body, the Chartered Association of Building Engineers (CABE), which was established in 1925. These accreditations would be in effect until July 2020.